Female Condom Use and Adoption Among Men and Women in a General Low-Income Urban U.S. Population. - Weeks, Margaret R; Zhan, Weihai; Li, Jianghong; Hilario, Helena; Abbott, Maryann; Medina, Zahíra (AIDS and behavior, 2015)
HIV prevention is increasingly focused on antiretroviral treatment of infected or uninfected persons. However, barrier methods like male condoms (MC) and female condoms (FC) remain necessary to achieve broad reductions in HIV and other sexually transmitted infections (STI). Evidence grows suggesting that removal of basic obstacles could result in greater FC use and reduced unprotected sex in the general population. We conducted four annual cross-sectional surveys (2009-2012) of urban residents (N = 1614) in low-income neighborhoods of a northeastern U.S. city where prevalence of HIV and other STIs is high. Findings indicate slow FC uptake but also heterosexual men's willingness to use them. Factors associated with men's and women's FC use included positive FC attitudes, network exposure, and peer influences and norms. These results suggest that men can be supporters of FC, and reinforce the need for targeted efforts to increase FC use in both men and women for HIV/STI prevention.